Q. 11

# ABC is and isosceles triangle whose ∠C is right angle. If D is mid point of AB, then let us prove that, AD^{2} + DB^{2} = 2CD^{2}

Answer :

Given: ABC is an isosceles triangle. So, AC = BC

∠C = right angle

To prove: AD^{2} + DB^{2} = 2CD^{2}

Proof:

By Pythagoras Theroem,

In ΔABC, We have

AB^{2} = AC^{2} + BC^{2}_{ } [1]

In ΔADC and ΔADB, we have

AC = BC [Given]

CD = CD [Common]

AD = DB [D is the mid point]

⇒ ΔADC ≅ ΔADB [By SSS Congruency Criterion]

⇒ ∠ADC = ∠ADB [Corresponding parts of congruent triangles are equal]

Also, ∠ADC + ∠ADB = 180° [Linear Pair]

⇒ ∠ADC + ∠ADC = 180°

⇒ ∠ADC = ∠ADB = 90°

Hence, ADC and ADB are right triangles, ∴ By Pythagoras theorem

AC^{2} = CD^{2} + AD^{2} [2]

BC^{2} = CD^{2} + BD^{2} [3]

Adding [2] and [3], we have

AC^{2} + BC^{2} = AD^{2} + BD^{2} + 2CD^{2}

⇒ AB^{2} = AD^{2} + BD^{2} + 2CD^{2}

⇒ (2AD)^{2} = AD^{2} + AD^{2} + 2CD^{2}

[∵ D is mid-point of AB, AD = BD and AB = 2AD = 2BD]

⇒ 4AD^{2} = 2AD^{2} + 2CD^{2}

⇒ 2AD^{2} = 2CD^{2}

⇒ AD^{2} + BD^{2} = 2CD^{2} [∵ AD = BD]

Hence, Proved!

Rate this question :

A person goes 24m. west from a place and then he goes 10m. north. The distance of the person from starting point is

West Bengal Board - MathematicsTwo rods of 13m. length and 7m. length are situated perpendicularly on the ground and the distance between their foots is 8m. The distance between their top parts is

West Bengal Board - MathematicsIf ABC is an equilateral triangle and AD ⊥ BC, then AD^{2} =

In ΔABC, if AB = (2a-1)cm. AC = 2 √2acm. And BC = (2a + 1)cm., then let us write the value of ∠BAC.

West Bengal Board - MathematicsIf the lengths of two diagonals of a rhombus are 24cm. and 10cm, the perimeter of the rhombus is

West Bengal Board - MathematicsIn the adjoining figure, the point O is situated within the triangle PQR in such a way that ∠POQ = 90°, OP = 6cm. and OQ = 8cm. If PR = 24cm. and ∠QPR = 90°, then let us write the length of QR.

West Bengal Board - Mathematics

I have drawn a triangle ABC whose height is AD. If AB>AC, let us prove that, AB^{2}-AC = BD^{2}-CD^{2}